Association Between Dietary Inflammatory Index and S-Klotho Plasma Levels in Middle-Aged and Elderly People - Ma, Teng-Chi; Zhou, Jing; Wang, Chen-Xi; Fang, Min; Gao, Feng (Frontiers in Nutrition, 2022)
Abstract Background and Aims: Soluble Klotho (S-Klotho) is a protein that has anti-aging properties . Dietary inflammation index (DII) is closely related to various age-related diseases. However, whether DII is related to S-Klotho plasma levels is still controversial. It was the goal of this study to examine the link between DII and S-Klotho in middle-aged and elderly people. Methods: Between 2007 and 2016, five NHANES cycles were conducted, with 12315 middle-aged and elderly (aged 40–79) participants having S-Klotho tests and submitting dietary recall data. The inflammatory potential of a diet was determined using the DII. To determine the plasma levels of S-Klotho, we employed a solid phase sandwich enzyme-linked immunosorbent assay (Elisa). Results: There was a negative correlation between DII and S-Klotho plasma levels . In the threshold effect analysis model, the break point was DII=1.3, and the negative correlation was more obvious when DII < 1.3 (β=-10.6，p=0.001). When DII > 1.3, the correlation disappeared (p=0.355). There may be a threshold saturation effect. Conclusion: In middle-aged and older individuals, there is a negative connection between the pro-inflammatory dietary pattern as evaluated by DII and the plasma level of S-Klotho. Given the rationale for the findings and the study's limitations, the fundamental mechanisms generating inflammation warrant additional exploration.